Kajian Penentuan Tarif Bus Trans Koetaradja berdasarkan Ability to Pay (ATP) dan Willingness to Pay (WTP) - Anggraini, Renni; Sugiarto, Sugiarto; Caisarina, Irin; Ahlan, Muhammad; Rahmani, Dhuyufur; Jalil, Erlinawati (Department of Civil Engineering, Diponegoro University, 2019)
Trans Koetaradja bus is managed by the government of Aceh Province to improve the urban public transport system. In order to appeal people to use this bus, the local government provides subsidy and applies the free fare, until today. It is expected that, when the subsidy is revoked in a few years ahead, people will get accustomed to use this bus. This research was conducted to observe public perceptions on the desired fare through ability to pay (ATP) and willingness to pay (WTP) analysis. Primary data was collected by doing survey over distributing questionnaires to the citizen. The bus corridors observed were on corridors I, III, and IV. The results showed that, the ATP-WTP of students were above the operator’s proposed tariff for all corridors. However, to attract those students to use the bus, it is recommended that the operator's proposed tariff (IDR 2,000 for each corridor) should be applied. For the general public category (PNS/TNI/Polri, Private Employees, Housewives, and other communities), the proposed tariff for each corridors were in between the average value of ATP-WTP. In that sense, tariff determination can be applied based on the average WTP value. However, the operator's proposed tariff for the public is still also feasible, subject to improving the level of services.